2018
DOI: 10.13005/ojc/340244
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization and Swelling study of Poly (Methacrylic acid-co-Maleic acid) Hydrogels

Abstract: A series of poly (methacrylic acid-Co-maleic acid), P(MAA-MA), hydrogels have been prepared by free radical polymerization in aqueous medium using different amount of maleic acid (MA) (0-5 wt.%), initiated by potassium persulfate (KPS) in the presence of N,N'-methylenebisacrylamide (MBA) as a crosslinking agent. Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA) and scanning electron microscope (SEM) techniques were used to characterize the prepared hydrogels. Their swelling behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Lampman et al (2010) [ 43 ] has stated that O-H group in carboxylic acid group would stretch, usually very broad (strongly H-bonded) and often overlap the C-H absorptions. Similarly, Harun et al (2019) [ 46 ] and Belkadi et al (2018) [ 47 ] have also reported a broad -OH peak around 3600 cm −1 to 3100 cm −1 . Peaks at 2985, 2884 cm −1 , 1449 cm −1 , and 753 cm −1 were assigned to the aliphatic carbons of the polymer chain backbone [ 48 ] (Bajpai et al 2009).…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…Lampman et al (2010) [ 43 ] has stated that O-H group in carboxylic acid group would stretch, usually very broad (strongly H-bonded) and often overlap the C-H absorptions. Similarly, Harun et al (2019) [ 46 ] and Belkadi et al (2018) [ 47 ] have also reported a broad -OH peak around 3600 cm −1 to 3100 cm −1 . Peaks at 2985, 2884 cm −1 , 1449 cm −1 , and 753 cm −1 were assigned to the aliphatic carbons of the polymer chain backbone [ 48 ] (Bajpai et al 2009).…”
Section: Resultsmentioning
confidence: 77%
“…So, completion of polymerization for both microspheres confirmed by the disappearance of C=C group in both spectra and has successfully being synthesized by using emulsion polymerization. Lastly, the signals at 1263 cm −1 to 1148 cm −1 indicated the presence of C-O group in the acrylate structure of nBA and carboxylic acid group of MAA [ 47 ]. Each peak in copolymers FTIR spectra ( Figure 4 a) shows an increase in transmittance intensity.…”
Section: Resultsmentioning
confidence: 99%
“…The absorption band of C-H and O-H bends were observed at 1465.90 and 1342.56 cm -1 . The peaks at 1100.44 cm -1 were attributed to C-O stretch [7], [32]. The absorption bands at ~3100 cm -1 (C-H stretch of vinyl group) and ~1600 cm -1 (conjugated C=C) were disappeared.…”
Section: Resultsmentioning
confidence: 97%
“…[ 38 ] In addition to these peaks, PMMA‐co‐MAA (curve (b)) also displays other peaks at 1250 and 1089 cm −1 that are associated with CO stretching and COC stretching. [ 39 ] In contrast, PMAA (curve (c)) reveals additional absorption peaks of OH stretching, CH stretching and CC stretching at 3468, 2930, and 1683 cm −1 , [ 40 ] respectively.…”
Section: Resultsmentioning
confidence: 99%